1998
DOI: 10.1108/09513559810225825
|View full text |Cite
|
Sign up to set email alerts
|

Non‐élite employees’ perceptions of organizational change in English local government

Abstract: Setting the sceneThis paper presents the findings of a major quantitative study of employee attitudes survey within eight English local authorities. A representative sample of eight English local authorities, two from each of the major authority types (London boroughs, metropolitan districts, county councils and "shire" districts) were selected. These four authority types represent the strategic local authorities in England. In London and the six other metropolitan conurbations (Greater Manchester, Merseyside,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Asquith (1998) found that communication accuracy weakens the further an employee is from the ''strategic centre' ' (pp. 265-266).…”
Section: Results-based Management Tools 221mentioning
confidence: 98%
See 1 more Smart Citation
“…Asquith (1998) found that communication accuracy weakens the further an employee is from the ''strategic centre' ' (pp. 265-266).…”
Section: Results-based Management Tools 221mentioning
confidence: 98%
“…Compared to line workers, for example, twice as many senior managers believed that organizational promotions were based on merit. Similarly, a study by Andy Asquith (1998) examined the perceptions of middle managers and ''street-level operatives'' regarding three different management styles among eight local governments in England. Asquith found that the further employees were from the ''organizational strategic centre,'' the weaker their commitment to the organization's objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use in colleges of business terms and job titles, such as chief executive or finance director, as discussed earlier, can be seen as an external manifestation of 'managerialism'. Incorporation precipitated the introduction into FE of managerialism which had begun, by that time, to pervade the public sector not just in the UK but also in a number of other countries (Asquith, 1998;Dixon et al, 1998). The significant impact of managerialism on the FE sector has been recognized and debated (Elliot and Crossley, 1997;Randle and Brady, 1997).…”
Section: Conditions Influencing the Representation Of Colleges As 'New College Hierarchies'mentioning
confidence: 99%
“…Extensive interviews were conducted with managerial and political elites to ascertain the nature of change management in the early 1990s. The findings were reported in Local Government Studies (Asquith, 1997), along with the results of an extensive employee attitudes survey in the eight authorities conducted at the same time (Asquith, 1998). Further, the article adds to the growing body of knowledge relating to the changing role of local authority chief executives (c.f.…”
Section: Introductionmentioning
confidence: 99%